Space, utopia and Indian decolonization - Banerjee, Sandeep, author.
1 online resource.
Keywords: The book illuminates the spatial utopianism of South Asian anti-colonial texts by showing how they refuse colonial spatial imaginaries to re-imagine the British Indian colony as the postcolony in diverse and contested ways. Focusing on the literary field of South Asia between, largely, the 1860s and 1920s, it underlines the centrality of literary imagination and representation in the cultural politics of decolonization. This book spatializes our understanding of decolonization while decoupling and complicating the easy equation between decolonization and anti-colonial nationalism. The author utilises a global comparative framework and reads across the English-vernacular divide to understand space as a site of contested representation and ideological contestation. He interrogates the spatial desire of anti-colonial and colonial texts across a range of genres, namely, historical romances, novels, travelogues, memoirs, poems, and patriotic lyrics. The book is the first full-length literary geographical study of South Asian literary texts and will be of interest to an interdisciplinary audience in the fields of Postcolonial and World Literature, Asian Literature, Victorian Literature, Modern South Asian Historiography, Literature and Utopia, Literature and Decolonization, Literature and Nationalism, Cultural Geography, and South Asian Studies.